LAJU KOROSI PADA SAMBUNGAN LAS RANGKA SEPEDA MOTOR: CORROSION RATE OF WELDING ON MOTORCYCLE FRAME - Sotya Anggoro (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
Corrosion is one of the things that occurs due to damage or degradation of metals due to a redox reaction between metals and various substances in their environment so that they can produce unwanted compounds. This corrosion is also often referred to as rusting. The process of this research was carried out by calculating the loss (weight loss) and analyzing the ratio of corrosion velocity, specimen changes, the ratio of fresh water and sea water and the ratio of specimens with coating and without coating. with a research time of 14 days. From the results of immersion analysis, comparison and calculation of specimens in the corrosion process yielded a value (mm/y), specimen 1 without coating corrosion value per year 0.37 (mm/y), specimen 2 without coating corrosion value per year 0.52 (mm/y ), specimen 1 with coating corrosion value per year 0.26 (mm/y), and specimen 2 with coating corrosion value per year 0.3 (mm/y). Overall, the research conducted on the corrosion of one of the four specimens, namely the specimen without coating, experienced a decrease in mass due to corrosion, from 54.09 g to 54.04 g. Uncoated specimens in the absence of protection have a higher corrosion rate